RESOURCE AND EXPLOITATION OF JUVENILE PENAEID PRAWNS FROM MANAKKUDY ESTUARY - Suseelan, C (Indian Journal of Fisheries, 2011)
The Manakkudy Estuary situated about 8 kilometres north of Cape Comorin in Tamil Nadu is an important source of juvenile penaeid prawns which are used as bait in hook-and-line fisheries and seed for culture, along the coasts of Kanyakumari District. It is estimated that 4 tonnes of juvenile prawns are exploited on an average every year from this environment, with peak catches in February and March. The fishery is constituted by Penaeus irulicus, P. monodon, Metapenaeus dobsord and M. monoceros. Of these, P. indicus is the most dominant species forming 90% of the total prawn catch. By following the progression of modes in (he size-frequency distribution it is estimated that males of this species grow at the rate of 24.3 mm|month and females, 26.2 mm|month. The maximum growth rates are recorded mostly